THE ROLE OF TECHNOLOGY IN ARABIC-INDONESIA TRANSLATION: TRANSFORMATION OF EDUCATION IN THE DIGITAL ERA - Budiarti, Arum Tri; Andani, Mirsa Tri; Fitria, Wira; Nasution, Sahkholid (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
This study examines the role of technology in Arabic-Indonesian translation, focusing on the opportunities and challenges it poses. The development of technology, especially artificial intelligence and machine translation, has significantly impacted the translation process and the world of education. On the one hand, technology offers opportunities to improve the efficiency, speed, and accessibility of translation. However, on the other hand, technology also presents challenges, such as accuracy, linguistic nuances, and the role of human translators. This study uses a qualitative descriptive method with literature review data collection techniques and content analysis to analyze how technology can be used to overcome these challenges and maximize existing opportunities so that it can produce quality and meaningful Arabic-Indonesian translations. The study results show that technology's role in Arabic-Indonesian translation provides opportunities and challenges. From the results of the study, it was found that the opportunities from AI-based translation, Google Translate, GPT chat, Online Dictionary, and so on can help someone who wants to learn a language with a very flexible, practical, and effective translation machine providing services for users, namely making it easier for someone to find the meaning of a vocabulary, sentence or Arabic text. Then, the existence of the translation machine also provides effectiveness and efficiency of time in translating a text or book, so that translating a text or book is completed faster in a short time. In addition to having opportunities or advantages in using technology translation machines. The role of technology translation also provides challenges or weaknesses in using translation machines. The weakness is the inaccuracy of the meaning produced by the translation machine. The meaning produced by the translation machine is sometimes confusing, inappropriate, and inaccurate. From the study results, researchers also showed that the comparison between the use of the Google Translate translation machine and the GPT chat translation machine, which is more effective and has 70% accuracy, is GPT chat.